Rising Mental Health Incidence Among Adolescents in Westchester, NY. - Rao, A. Ravishankar; Rao, Saroja; Chhabra, Rosy (Community Mental Health Journal, 2022)
Context: Many governments have publicly released healthcare data, which can be mined for insights about disease conditions, and their impact on society. Methods: We present a big-data analytics approach to investigate data in the New York Statewide Planning and Research Cooperative System (SPARCS) consisting of 20 million patient records. Findings: Whereas the age group 30–48 years exhibited an 18% decline in mental health (MH) disorders from 2009 to 2016, the age group 0–17 years showed a 5.4% increase. MH issues amongst the age group 0–17 years comprise a significant expenditure in New York State. Within this age group, we find a higher prevalence of MH disorders in females and minority populations. Westchester County has seen a 32% increase in incidences and a 41% increase in costs. Conclusions: Our approach is scalable to data from multiple government agencies and provides an independent perspective on health care issues, which can prove valuable to policy and decision-makers.